Proposed Model for the Reduction of Overweight in Table Grape Packaging with Lean Manufacturing and Ergonomics Techniques in an Agro-Industrial Company - Ochoa-Vásquez, Rita L. (2022)
The agro-industrial sector is constantly growing worldwide, continuously improving both at the level of machines and at the productive level. However, it can be affected by various problems such as specification control, production control, among others; there is one, the overweight. Overweight is generated by failing to comply with the specifications of the "packaging regulations", in which it is mentioned that the grapes when packaged must have a surplus of 3% to 5%. Therefore, exceeding the limits can have as consequences loss of utility, productivity. To this is added the lack of a correct study of the job, causing the operators to accumulate work fatigue and, consequently, a decrease in their work rate. It is for this reason that, using Lean tools, such as SPC and Work Standardization, and ergonomic techniques, such as the OWAS method, an improvement proposal is proposed that manages to outline and solve the problems of the case study. This will optimize and minimize, through a joint implementation, the problem of overweight in boxes with the increase in the productivity of the operators to 20%, the increase of control and review of the quality and production area by 10% and 14%, respectively, and the reduction of the variability in the working methods to 50%.